ANALISIS TINGKAT RISIKO KREDIT PADA PT. BANK SULUT, TBK DI MANADO - Fabiola Brigitta Coragneta Tamon; Tineke M. Tumbel; Ventje Tatimu (JURNAL ADMINISTRASI BISNIS, 2016)
This study is based on that bank is a business entity that collects funds from the public in the form of savings and channel them back to the community in the form of loans. The general activities of banks as a financial intermediary is basically memobalisasi funds from the public for further distribution to individuals or institutions that need the funds in the form of loans or credit. Credit is one part of capital formation carried out by financial institutions, in this case the banks to the public in order to boost the performance of the business, so it can be used to improve the productivity of the real sector which is done by people individually or in groups. The purpose of this study was to determine how much the level of credit risk at PT. Bank of North Sulawesi, Tbk in Manado. This research uses descriptive quantitative approach using financial ratio analysis through NPL. Credit risk is known as non-productive loans for the banking sector. Bank Indonesia classifies non prduktif credits in three categories: category substandard, doubtful and loss. The level of the average NPL ratio of 0.17% in the period December 31, 2012 until 30 September 2013 period, the ratio is very good because it still remains far below the tolerance level of NPLs is set by BI at 5% the amount of non-performing loans (NPL).Keywords: Credit risk, bank